Obscuring complexity and performing progress: unpacking SDG indicator 6.5.1 and the implementation of IWRM - Mdee, A.; Ofori, A. D.; Cohen, J.; Kjellén, M.; Rooney, E.; Singhal, S.; Amezaga, J.; Ankush; Figueroa-Benítez, A.; Gupta, S.; Haile, Alemseged Tamiru; Haileslassie, A.; et al. (Water Alternatives Association, 2024)
At a rhetorical level, the SDGs provide a unified global agenda, and their targets and indicators are believed to drive action for social and environmental transformation. However, what if the SDGs (and their specific goals and indicators) are more of a problem than a solution? What if they create the illusion of action through a depoliticised and technical approach that fails to address fundamental dilemmas of politics and power? What if this illusion continues to reproduce poverty, inequality, and environmental degradation? This paper addresses these questions through a focus on SDG 6.5.1 – the implementation of integrated water resources management (IWRM), measured on a 0-100 scale through a composite indicator. The paper presents an empirical analysis of SDG 6.5.1 reporting in Colombia, Ethiopia, India, Malaysia, and the UK, drawing on research from the Water Security and Sustainable Development Hub.1 An evidence review and series of expert interviews are used to interrogate the local politics of IWRM measurement, specifically three dilemmas of global composite indicator construction: (1) reductive quantification of normative and contested processes; (2) weak analysis of actually existing institutional capability, politics, and power; and (3) distracting performativity dynamics in reporting. The paper concludes that SDG 6.5.1 is an example of a 'fantasy artefact', and that in all countries in this study, IWRM institutions are failing to address fundamental and 'wicked' problems in water resources management. We find little evidence that these numbers, or the survey that gives rise to them, drive meaningful reflection on the aims or outcomes of IWRM. Instead, they tend to hide the actually-existing political and institutional dynamics that sit behind the complexity of the global water crisis.